Prevalence, clinical reasons and associated factors of extended treatment duration for drug susceptible tuberculosis – a real-world experience - Chih-Yu Liu; Rou-Tsern Chen; Chin-Chung Shu; Shu-Yung Lin (Scientific Reports)
Abstract Limited research has been conducted on the prevalence and factors associated with extended drug-susceptible tuberculosis (TB) treatment. A retrospective study enrolled drug-susceptible TB patients (January 2018 to December 2020) from a hospital’s registry to analyze prevalence, reasons, and factors for extended treatment (≥ 9 months) compared with standard course. Analyzing 221 TB patients, 80 patients received extended treatment. The extended group showed higher hepatitis B infection rates (12.5% vs. 5%, p = 0.043), recent cancer treatment (18.8% vs. 8.5%, p = 0.025), more adverse drug events (ADEs) (grade 3 or more severe ADEs 27.5% vs. 11.3%, p = 0.003), and treatment interruptions (46.3% vs. 18.4%, p < 0.001). Logistic regression highlighted hepatitis B infection (AOR 3.10, p = 0.039), recent cancer treatment (AOR 3.09, p = 0.013), and post-treatment elevated aminotransferase (AOR 2.40, p = 0.014) as independent factors for extended treatment. Extended anti-TB treatment affects 28.7% of patients, with host characteristics and adverse drug effects playing a role in treatment duration. Integrating these factors into treatment strategies is vital for optimal patient care.